Morphology, mechanical strength and degradation of polyhydroxyalkanoate scaffolds - Arroyave-Muñoz, Liliana Maria; Ossa-Orozco, Claudia Patricia (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Tissue engineering (TE) seeks to improve the unsatisfactory development of implants and medical procedures to solve bone and cartilage injuries. TE aims at regenerating tissues using cell growth platforms (scaffolds), which may consist of natural polymers such as polyhydroxyalkanoate (PHA). PHA is an innovative material useful in medical applications due to its degradation capability and bacterial origin that allows large-scale production and control final properties. In this research, we developed commercial PHA scaffolds using the lyophilization technique with a factorial experimental design. We used dichloromethane as PHA solvent, tergitol as surfactant, and liquid nitrogen (N2) for the freezing process. We characterized the PHA by Fourier-transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA); and the scaffolds by scanning electron microscopy (SEM) and mechanical compression and hydrolysis degradation tests. The characterization of the PHA indicated that the material is a mixture of PHA and polylactic acid (PLA). The results showed a suitable pore distribution for migration of chondrocytes through the scaffold, in addition to a behavior similar to that of the articular cartilage, although it presented lower mechanical strength. Also, the scaffolds displayed mass loss in a non-linear way related to the percentage of PHA present in the sample. In conclusion, PHA scaffolds have a potential use in tissue engineering for restoring articular cartilage.